Cognitive map recall test: A new specific test to assess topographical disorientation - Descloux, Virginie; Maurer, Roland (Applied neuropsychology. Adult, 2018)
Topographical disorientation, the inability to orient in a well-known environment, is a very incapacitating syndrome. Despite its relatively high frequency after a right cerebral lesion, there is currently no specific neuropsychological test to assess it. We propose a completely new test, with preliminary normative data, assessing the subjects' ability to recall allocentric spatial information from their cognitive map. The subjects are asked to mentally compare distances and directions between landmarks in their familiar environment. This necessitates creating an individual version of the test tailored to every participant's knowledge. This task was proposed to 53 patients with a right lesion and a control group (N = 133). We evaluated performance at comparing distances and directions, and the impact of sociodemographic variables (age, gender, and education). Results show that a right cerebral lesion leads to difficulties in evoking and comparing allocentric spatial information, and more specifically in judging directions. Furthermore, the results show an impact of age, but not gender nor education, on recalling information from a cognitive map. Although there are some intrinsic difficulties (for example in creating patient-specific versions of the test), preliminary normative data indicate that this original test is workable and provides important information in assessing topographical disorientation in clinical practice.